BIMBINGAN TEKNIS PEMASANGAN PIPA POLYETHYLENE UNTUK SISTEM AIR BERSIH BANJAR KAJA-KAUH DESA SUDAJI - Suweden, I N.; Suryawan, A.A.A.; Dana, I W.; Arsana, I G.N.K. (Buletin Udayana Mengabdi; Vol 15 No 2 (2016): Jurnal Udayana Mengabdi, 2016)
Kaja-Kauh sub-village of Sudaji village is a nestled community in the hills, with a population of 231 households (1,155 people), until now could not enjoy clean water because there are constraints on the piping system. In order to meet the needs of everyday people have to carry water from source water from other villages higher elevation, such as Sekumpul and Lemukih villages using a piping system. In this activity, the pipe material provided by the Rotary Club Bali-Taman in collaboration with the Korean Rotary Club. While the physical execution of the installation of the pipeline in the field of mutual assistance is done by local people. Given the pipe material given is kind of a new pipe is a pipe High Density Poly Ethylene (HDPE) that is not yet known by the public, especially in the process of these connections by using a system of compression joint, the team of Udayana University needs to provide technical assistance in the form of guidance and supervision of the implementation of pipe laying. After receiving technical assistance from the implementation team devotion Udayana University, the community has been able to install and connect HDPE pipe properly. Water has been flowing smoothly, both from the water spring to the reservoir and from the reservoir to residents housing. But not all houses connected to water systems because of the constraints of society's ability to provide pipes and water meter that must be provided by each water user.
Keywords: clean water; HDPE pipe; Sudaji village; Kaja-Kauh sub-village